Integrating hydrogen justice with infrastructure engineering - Shrimpton, Elisabeth A.; Balta-Ozkan, Nazmiye (MDPI, 2026)
Hydrogen produced with net zero CO2 (H2NZ) has a significant role to play in a sustainable energy transition. Often overlooked are the different means of producing H2NZ with different trade-offs that will impact communities in diverse ways. Science and engineering need to be part of the dialogue so the nuances of these technologies can be understood and just solutions generated. However, there is little direct engagement with science and engineering in the energy justice literature. To address this gap, a workshop of expert engineers and social scientists is used to analyse four developing H2NZ technologies with justice issues. The results propose a way forward to integrate engineering with the energy justice discourse and, at the same time, encourage social science to reach out to engineering. The outcome and novelty are a suite of questions that integrate disciplinary perspectives and offer a means of encouraging context and technologically sensitive outcomes.
This article belongs to the Section Energy Sustainability
Keywords: 4004 Chemical Engineering; 40 Engineering; 33 Built Environment and Design; Bioengineering; 7 Affordable and Clean Energy; hydrogen justice; interdisciplinarity; energy transition; socio-technical systems; Sustainable Development Goal 7